The Role of Home Gardens in Enhancing Food Security and Biodiversity in Pujon District, East Java: Insights From Local User’s Value Index (LUVI) Analysis - Tika Putri Agustina; Musma Rukmana; Fernando Andre Watung; Kurniahtunnisa; Mellyatul Aini (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Homegardens have long been a vital traditional agroforestry system supporting the livelihoods of Indonesian communities, particularly in terms of food security. This study aims to deepen the understanding of the role of homegardens in national food security by focusing on a case study of the Local User Value Index (LUVI) for food crops in homegardens in Pujon, Malang Regency, East Java. The research methodology involved collecting local knowledge from the community and applying the Pebble Distribution Method (PDM) to calculate the significance value of plants across various utility categories (LUVI). The findings indicate that homegardens play a significant role in meeting local food needs, particularly through the production of food crops, vegetables, fruits, herbs, and natural dyes. Crops such as maize and cassava serve as important staple food alternatives in areas with limited agricultural land. The preference for plant usage is influenced by geographical factors, community preferences, and the utility of the plants. This study provides deeper insights into the potential of homegardens and their role in supporting food security, with the aim of contributing to the advancement of knowledge and agricultural policy development in the future.